TEACHERS’ BELIEFS ABOUT THE NATURE OF MATHEMATICS, MATHEMATICS LEARNING, AND MATHEMATICS TEACHING (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
As in the findings of earlier studies (e.g., Alamu, 2010; Cross, 2009; Thompson, 1984; Whitehouse, 2003), teachers in this study were found to hold beliefs about the nature of mathematics, mathematics learning, and mathematics teaching that reflect a combination of traditional and constructivist perspectives to varying degrees.